2003
DOI: 10.1002/neu.10261
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates to flight‐related density‐dependent phase characteristics in locusts

Abstract: Locust phase polymorphism is an extreme example of behavioral plasticity; in response to changes in population density, locusts dramatically alter their behavior. These changes in behavior facilitate the appearance of various morphological and physiological phase characteristics. One of the principal behavioral changes is the more intense flight behavior and improved flight performance of gregarious locusts compared to solitary ones. Surprisingly, the neurophysiological basis of the behavioral phase characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…These included all reported differences in morphometric ratios, coloration and pattern, and development. Further, recently reported neurophysiological differences (Fuchs et al, 2003) and behavioral differences (Geva et al, 2010) are also very robust and consistent.…”
Section: Laboratory-reared Locusts Approach the Two Extreme Density-dsupporting
confidence: 68%
See 2 more Smart Citations
“…These included all reported differences in morphometric ratios, coloration and pattern, and development. Further, recently reported neurophysiological differences (Fuchs et al, 2003) and behavioral differences (Geva et al, 2010) are also very robust and consistent.…”
Section: Laboratory-reared Locusts Approach the Two Extreme Density-dsupporting
confidence: 68%
“…In locusts, gregarious animals are characterized by diurnal flight behavior, while solitary locusts fly at night. Fuchs et al (2003) describe an identified flight-related inhibitory interneuron, which is sensitive to illumination level, and show a remarkable and highly significant increase in activity during the dark but only when locusts are crowded locusts. Lastly, serotonin (5-hydroxtryptamine, 5HT) is both necessary and sufficient for locust phase transformation, with increasing levels of 5HT accompanying (and inducing) gregariousness (Anstey et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the larger brains of gregarious locusts are more dedicated to the integration of sensory cues in higher level processing regions, which is thought to support their lifestyle as generalist foragers in dense, migratory swarms where competition among group members is high (Ott and Rogers, 2010). Other changes in brain functioning situate at the level of circuit activity and function (Ayali et al, 2004; Blackburn et al, 2010; Burrows et al, 2011;Fuchs et al, 2003). For example, gregarious L. migratoria show reduced habituation of interneuron activity in response to approaching objects.…”
Section: Introductionmentioning
confidence: 99%
“…There are also clear differences in specific neuronal circuits and muscular systems between the two extreme locust phases that can be related to these differences in behaviour (Matheson et al, , 2004Blackburn et al, 2003;Fuchs et al, 2003). The neuro-hormonal mechanisms that drive and maintain phase change, however, remain largely unknown (Pener, 1991;Pener and Yerulshami, 1998;Breuer et al, 2003).…”
mentioning
confidence: 99%